The right thing to do : (McGraw-Hill, 2003)
The Right Thing To Do is a collection of readings in moral theory and moral issues from major Western philosophers. It is the successful companion reader for Rachels' text, The Elements of Moral Philosophy. This anthology explores further the theories and issues introduced in that volume, in their original and classic formulations. The collection can stand on its own as the text for a course in moral philosophy, or it can be used to supplement any introductory text.